DEFENSA DEL RECURSO ALIMENTICIO POR ASTYLUS RUBRICOSTATUS GERMAR, 1824 (INSECTA: COLEOPTERA: MELYRIDAE) (Acta Entomológica Chilena, 2022)
Adults of Astylus rubricostatus deferid inflorescences of the herb Gaillardia megapotamica var radiata(Griseb) Baker against intrusión by conspecific individuáis. It is probable that the behaviour is a result fromcompetition among individuáis of both sexes for the amount of polen contained by flowers of G. megapotamica, which seems to be the limiting resource.